Forest products: from marking to market - Colorado State Forest Service, author (Colorado State University. Libraries, 2013)
The purpose of this guide is to provide forest landowners the information and tools they need to help them successfully implement forest stewardship activities utilizing contracted services. The guide focuses on the steps a landowner should take to set up and implement a forest products sale from developing a forest stewardship plan to overseeing the sale. The information also is applicable to preparing a forestry project for which the property owner pays a contractor for the work to be performed. Landowners who want to cut trees and/or make their own product to sell (i.e. fencing material, furniture, split firewood) also will find pertinent information in this guide. Landowners conducting their first sale or project are encouraged to partner with a professional forester.
Keywords: forest stewardship; forest products market; planning; preparation; selling; contract; marketing